Metabolome and Transcriptome Integration Reveals Insights Into Flavor Formation of ‘Crimson’ Watermelon Flesh During Fruit Development - Gong, Chengsheng; Diao, Weinan; Zhu, Hongju; Umer, Muhammad Jawad; Zhao, Shengjie; He, Nan; Lu, Xuqiang; Yuan, Pingli; Anees, Muhammad; Yang, Dongdong; Kaseb, M. O.; Liu, Wenge (Frontiers in Plant Science, 2021)
Watermelon is a major horticultural crop cultivated worldwide, and the research on the flavor-related metabolites of watermelon flesh is concerned by consumers. But the dynamics of multiple metabolic changes during watermelon fruit development and the regulatory networks are poorly understood. In this work, a total of 517 metabolites were detected in 'Crimson' watermelon fruit of different developmental stages by UPLC-ESI-MS/MS and GC-SPME-MS. At the same time, we combined the K-means hierarchical clustering method to analyze differential accumulation metabolites and differentially expressed genes with similar accumulation patterns, respectively. Moreover, we enriched the taste-related important metabolites and genes into the primary metabolite synthesis pathway and enriched the aroma-related metabolites and genes into the lipoxygenase pathway. Furthermore, through co-expression analysis, five differentially expressed ADH (Alcohol dehydrogenase) genes (Cla97C01G013600, Cla97C05G089700, Cla97C01G001290, Cla97C05G095170, and Cla97C06G118330) were closely related to related alcohols/aldehydes and provides insights into the formation of fruit aroma. Our findings provide insights into the metabolomic variations and molecular mechanisms of flavor related metabolites in watermelon flesh at different developmental stages.